2005
DOI: 10.1038/modpathol.3800438
|View full text |Cite
|
Sign up to set email alerts
|

EGFR gene amplification in breast cancer: correlation with epidermal growth factor receptor mRNA and protein expression and HER-2 status and absence of EGFR-activating mutations

Abstract: The human epidermal growth factor receptor (HER) family of receptor tyrosine kinase has been extensively studied in breast cancer; however, systematic studies of EGFR gene amplification and protein overexpression in breast carcinoma are lacking. We studied EGFR gene amplification by chromogenic in situ hybridization (CISH) and protein expression by immunohistochemistry in 175 breast carcinomas, using tissue microarrays. Tumors with 45 EGFR gene copies per nucleus were interpreted as positive for gene amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
241
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(261 citation statements)
references
References 29 publications
17
241
1
2
Order By: Relevance
“…Proteolytic digestion: We 4,27 and others 15,18 demonstrated that the tissue digestion solution from SPoT-Light Tissue Pretreatment Kit (Zymed) provides consistent results. For all commercially available probes tested, we observed that digestion for o4 min leads to total absence of signals in the majority of tissues, whereas digestion for 410 min results in poor morphological features and blurred signals.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Proteolytic digestion: We 4,27 and others 15,18 demonstrated that the tissue digestion solution from SPoT-Light Tissue Pretreatment Kit (Zymed) provides consistent results. For all commercially available probes tested, we observed that digestion for o4 min leads to total absence of signals in the majority of tissues, whereas digestion for 410 min results in poor morphological features and blurred signals.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, with the advent of tissue microarrays, ISH experiments can now be performed in a high throughput fashion. [13][14][15][16] This has been elegantly demonstrated by several groups using both fluorescent (FISH) 13,14 and chromogenic ISH (CISH). 15,16 Although FISH provides accurate copy number assessment, this technique is not ideally suited for TMAs, as fluorescent microscopy does not allow an optimal correlation between copy numbers and cytomorphological aspects of the cells and it proves difficult and time consuming to navigate through the tissue microarray section under a fluorescent microscope.…”
mentioning
confidence: 99%
“…In colorectal and breast cancers, amplification of the EGFR gene is invariably associated with overexpression of EGFR. 18,19 However, cancers that overexpress EGFR do not always show amplification of the EGFR gene, 19 indicating that amplification of the EGFR gene causes EGFR overexpression, but EGFR overexpression is not always caused by EGFR gene amplification. Our study indicated that EGFR overexpression in the serous cystic neoplasms is associated with an increase in the copy number of transcripts without amplification of the EGFR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant signaling involving the EGFR and its downstream molecules is implicated in the development of cancers of the head and neck, breast, lung, colon, and pancreas. [16][17][18][19][20][21] Recently, EGFRs have come to be regarded as clinically important because of the development of a number of anti-EGFR drugs, including extracellular domain-targeted antibody-based drugs such as cetuximab, panitumumab, and zalutumumab, and intracellular kinase domain-targeted smallmolecule-based drugs such as erlotinib and gefitinib. These drugs enable the medical treatments of some cancers.…”
mentioning
confidence: 99%
“…EGFR amplification and activating mutations are rare events in breast cancer and differences in EGFR expression appear to be controlled largely at the transcriptional level. 45,48 By contrast, it is well-established that about 20% of breast carcinomas are characterized by HER2 gene amplification, leading to an excess of HER2 protein in cancer cells and a high risk of recurrences (reviewed in ref. 49).…”
Section: Impact Of Fhit On Her2-driven Breast Tumorsmentioning
confidence: 99%